STUDYING OF FLAVONOIDS IN THE FILM “HEMOSTAT” (International Scientific Journal Alfraganus, 2025)
The development of the pharmaceutical industry involves ensuring rapid and stable growth. This includes saturating the domestic market with high-quality, safe, and affordable medicines produced locally, expanding sources of local raw materials, and increasing the production of drugs that re- place imports.
Keywords: film; Na-KMS; flavonoids; quantitative analysis; HPLC